2005
DOI: 10.1097/01213011-200504000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microsomal triglyceride transfer protein promoter polymorphism −493 GT on fasting plasma triglyceride values and interaction with treatment response to atorvastatin in subjects with heterozygous familial hypercholesterolaemia

Abstract: Familial hypercholesterolaemia (FH) is an autosomal dominant disease characterized by elevated levels of low-density lipoprotein-cholesterol (LDL-C). Phenotypic expression is highly variable, being influenced by diet, age, gender, body mass index, apolipoprotein E genotype and type of LDL-receptor gene mutation. Microsomal triglyceride (TG) transfer protein (MTP) is a protein involved in lipid metabolism. Polymorphism MTP -493 GT has been shown to modulate lipid levels in several populations. To analyse the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Since oleate [Qiu et al, 2005] as well as polyunsaturated fatty acids [Sekiya et al, 2003] reduce SREBP-1 activity, the resulting abrogate suppression of MTTP could be more effective in À164T than in À164C carriers. This possible diet-gene interaction may explain conflicting results of association studies [Bernard et al, 2000;Berthier et al, 2004;Bjorn et al, 2000;Chen et al, 2003;Couture et al, 2000;Garcia-Garcia et al, 2005;Herrmann et al, 1998;Juo et al, 2000;Karpe et al, 1998;Ledmyr et al, 2002Ledmyr et al, , 2004Lundahl et al, 2002Lundahl et al, , 2006Phillips et al, 2004;Rubin et al, 2006;St-Pierre et al, 2002;Stan et al, 2005;Yamada et al, 2006] and should be tested in intervention studies or case-control cohorts. Notably, polymorphic sites in the SREBP1 locus are associated with type 2 diabetes and obesity [Eberle et al, 2004;Laudes et al, 2004].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Since oleate [Qiu et al, 2005] as well as polyunsaturated fatty acids [Sekiya et al, 2003] reduce SREBP-1 activity, the resulting abrogate suppression of MTTP could be more effective in À164T than in À164C carriers. This possible diet-gene interaction may explain conflicting results of association studies [Bernard et al, 2000;Berthier et al, 2004;Bjorn et al, 2000;Chen et al, 2003;Couture et al, 2000;Garcia-Garcia et al, 2005;Herrmann et al, 1998;Juo et al, 2000;Karpe et al, 1998;Ledmyr et al, 2002Ledmyr et al, , 2004Lundahl et al, 2002Lundahl et al, , 2006Phillips et al, 2004;Rubin et al, 2006;St-Pierre et al, 2002;Stan et al, 2005;Yamada et al, 2006] and should be tested in intervention studies or case-control cohorts. Notably, polymorphic sites in the SREBP1 locus are associated with type 2 diabetes and obesity [Eberle et al, 2004;Laudes et al, 2004].…”
Section: Discussionmentioning
confidence: 91%
“…In humans, loss-of-function mutations of MTTP resulted in hypo-and abetaliproteinemia associated with hypocholesterolemia, mild fat malabsorption, and hepatic steatosis [Linton et al, 1993;Scanu et al, 1974]. The physiological importance of MTTP was also emphasized by association studies, which provide evidence that a haplotype, defined by the minor alleles of polymorphisms Ile128Thr, À164T4C, and À493G4T, is associated with a slight decrease in LDL cholesterol and other traits of the metabolic syndrome [Bernard et al, 2000;Bjorn et al, 2000;Garcia-Garcia et al, 2005;Karpe et al, 1998;Ledmyr et al, 2002Ledmyr et al, , 2004Lundahl et al, 2006;Phillips et al, 2004;Rubin et al, 2006;St-Pierre et al, 2002;Yamada et al, 2006]. Here we provided functional investigations of MTTP promoter haplotypes composed of polymorphisms À164T4C, À400A4T, and À493G4T in human hepatic and intestinal cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The TT subjects, as a whole, showed a significantly higher response in reducing fasting cholesterol, apo B-48, TRL phospholipids, 16:0, and 18:1 and in increasing 18:2 values, but only TT men showed a major improvement of the Framingham score. This sex-related sensitivity to diet can be linked to the recent finding that, in men with familial hypercholesterolemia but not in women, this polymorphism modulated after-treatment plasma triacylglycerol values (32).…”
Section: Discussionmentioning
confidence: 99%
“…Single studies have reported that a promoter variant in MTP is associated with triglyceride response and recurring risk of coronary events, an LPL variant may alter TC or HDLC response, and an LIPC variant may alter HDLC response. [79][80][81][82][83][84][85] Removal of cholesterol from peripheral cells requires active transport and is mediated by ABCA1. Preliminary pharmacogenetic analysis suggests that an ABCA1 haplotype may attenuate ApoAI response to statin treatment.…”
mentioning
confidence: 99%